Heterologous Ectoine Production in Escherichia coli: Optimization Using Response Surface Methodology - I Putu Parwata; Deana Wahyuningrum; Sony Suhandono; Rukman Hertadi (International Journal of Microbiology)
Introduction. A halophilic bacterium of the Halomonas elongata BK-AG25 has successfully produced ectoine with high productivity. To overcome the drawbacks of high levels of salt in the production process, a nonhalophilic bacteria of Escherichia coli (E. coli) was used to express the ectoine gene cluster of the halophilic bacteria, and the production of ectoine by the recombinant cell was optimized. Methods. The ectoine gene cluster from the halophilic bacterium was isolated and inserted into an expression plasmid of pET30(a) and subsequently transformed into E. coli BL21 (DE3). Production of ectoine from the recombinant E. coli was investigated and then maximized by optimizing the level of nutrients in the medium, as well as the bioprocess conditions using response surface methodology. The experimental designs were performed using a central composite design. Results. The recombinant E. coli successfully expressed the ectoine gene cluster of Halomonas elongata BK-AG25 under the control of the T7 promoter. The recombinant cell was able to produce ectoine, of which most were excreted into the medium. The optimization of ectoine production with the response surface methodology showed that the level of salt in the medium, the incubation temperature, the optical density of the bacteria before induction, and the final concentration of the inducer gave a significant effect on ectoine production by the recombinant E. coli. Interestingly, the level of salt in the medium and the incubation temperature showed an inverse effect on the production of intracellular and extracellular ectoine by the recombinant cell. At the optimum conditions, the production yield was about 418 mg ectoine/g cdw (cell dry weight) after 12 hours of incubation. Conclusion. This study is the first report on the expression of an ectoine gene cluster of Halomonas elongata BK-AG25 in E. coli BL21, under the control of the T7 promoter. Optimization of the level of nutrients in the medium, as well as the bioprocess condition using response surface methodology, has successfully increased the production of ectoine by the recombinant bacteria.